Penggunaan Ayat-ayat Al-Qur’an dalam Pengobatan Tradisional (Ruqyah) Pada Komunitas Jam’iyyah Ruqyah Aswaja (JRA) di Samarinda - Putri Ameda; Mursalim Mursalim (JIA (Jurnal Ilmu Agama), 2025)
This study examines the use of Qur'anic verses in the ruqyah practice conducted by the Jam’iyyah Ruqyah Aswaja (JRA) Community in Samarinda, focusing on the implementation of ruqyah, the verses used, the basis for their selection, and public perceptions of its effectiveness as a healing method. Using a qualitative approach and descriptive methods, data were collected through interviews with ruqyah practitioners, direct observation, and document analysis. The findings reveal that the ruqyah methods employed by JRA Samarinda are flexible but firmly rooted in the belief that the Qur'an serves as Asy-Syifa' (a source of healing). Surahs such as Al-Fatihah, Ayat Kursi, Al-Falaq, An-Nas, and other verses are selected based on their relevance to the type of illness, the meaning of the verses, the asbabun nuzul (reasons for revelation), or stories within the Qur'an. This selection process also involves empirical experience, testing (tajrib), and authorization from scholars with a sanad (chain of transmission) in ruqyah knowledge. The Samarinda community generally accepts ruqyah as an effective alternative healing method, though further understanding of its concepts is still needed. This research is expected to enrich Living Qur'an studies, particularly in the context of ruqyah therapy, while also offering practical benefits for society in utilizing Qur'anic verses as an effective spiritual healing solution